Association between inflammatory biomarkers and gestational diabetes mellitus in women aged 20–44: a cross-sectional analysis of NHANES 2007–2018 - Jinsheng Li; Qianwen Zhang; Xi Wang; Xin Fu; Lei Chen (Gynecological Endocrinology)
Inflammation exerts an essential role in gestational diabetes mellitus (GDM), but the relationship between peripheral blood inflammatory markers and GDM remains unclear. The purpose of this study was to explore the relationship between inflammatory markers and GDM in US adults. Data were extracted from the National Health and Nutrition Examination Survey. Five inflammatory markers were derived from complete blood count. Survey-weighted multivariable logistic regression models were used to assess the association between inflammatory markers and GDM. Restricted cubic splines and subgroup analyses were conducted to validate the stability of the results. Finally, a total of 2363 women aged 20–44 were included based on specific criteria, with 229 self-reported GDM cases (9.69%). The increased lymphocyte–monocyte ratio (LMR) was associated with the higher risk of GDM, aOR = 1.82 (CI:1.30–2.56). Compared with the lowest tertile, the highest tertile group of LMR showed a significantly increased risk of GDM, aOR = 2.24 (CI: 1.28–2.85). Conversely, the highest tertile group of systemic inflammation response index (SIRI) was negatively associated with GDM, aOR = 0.61 (95% CI: 0.40–0.94). And high platelet–lymphocyte ratio (PLR) levels are related to a lower risk of GDM. No non-linear relationships were observed. Furthermore, subgroup analysis revealed that the association between LMR, SIRI, and GDM remained consistent with the overall results. Our study indicated that LMR, PLR, and SIRI may be potential predictors of GDM. Further large-scale prospective study is needed to investigate the role of LMR, PLR and SIRI in GDM.